Investigation of process yield in the transesterification of coconut oil with heterogeneous calcium oxide catalyst - Velasquez, Jo Marie; Kang Suk, Jhun; Bugay, Byron; Razon, Luis F., Dr.; Tan, Raymond R., Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/